The adoption of artificial intelligence (AI)-based technologies for road cycling safety in Metro Manila a technology foresight - Rance, Mario L.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, 2022)
The onset of the Covid-19 pandemic had been an eye-opener to the government and to everyone to adopt and make a drastic shift from old and conventional processes to new solutions using innovative technologies.
In the time of the fourth industrial revolution where emerging and disruptive technologies such as Artificial Intelligence (AI) have continued to create applications in different industries, create new business models and innovations that have replaced labor-intensive and repetitive jobs. It has not been just a technological trend but also a political trend as many countries continue to adopt AI technology, especially in this pandemic.

Many government agencies supported cycling as an alternative mode of transportation to recover the economy since the significant transportation modes have been limited. As a result, many commuters shifted to this active transportation mode, and many "new-born cyclists" have been noticeable on main roads in Metro Manila. Moreover, various government projects and programs in construction of bike facilities and infrastructure have been implemented, the opportunity to integrate new technologies such as AI has seen considerable.

The paper aimed to incorporate the significance of AI-based technologies and the safety it could give in the future of transportation, particularly in the active transport sector. This paper showcased the existing AI technologies being developed and its possible integration into the current Intelligent Transport System (ITS). It aimed to assess the political, economic, social, environmental, technological, and legal factors that may influence AI-based technologies' adaptation for the next five (5) to ten (10) years.

The study was able to lay future scenarios that can be used as a reference by government policy-making agencies through a holistic and technology-driven approach in making strategic and technological roadmaps for major roads in Metro Manila.
The study is expected to help the government create sustainable, equitable, and safe roads for every active transport commuter, especially the cyclists, in Metro Manila through the use of new and emerging technologies such as Artificial Intelligence.
Thesis
Keywords: Artificial intelligence